Valuation of renewable and unconventional electricity sources: An approach from real options [Avaliação de fontes renováveis não convencionais de geração de energia: Um enfoque a partir das opções reais] [Valoración de fuentes renovables no convencionales de generación de electricidad: Un enfoque desde las opciones reales] (2015)
In this paper the investment opportunities in emerging power generation technologies, which are considered risky investments due to the volatility of the market price of electricity, are valuated. This analysis uses both the theoretical framework for valuing real options proposed by Dixit and Pindyck (1994) and theoretical information of investment and operational costs for the technologies being analyzed. The model allows a calculation of the value of the investment opportunity and the optimal trigger price to invest in these technologies within the Colombian electricity market conditions. Results show that under current market conditions investors should defer the investment until a required optimal trigger price is found, results which also correspond to the pattern observed in the Colombian market. © 2015, Pontificia Universidad Javeriana. All Rights Reserved.